Three-year Experience of Antimicrobial Stewardship in a Tertiary Care Hospital in Pakistan: Successes and Challenges - Naseem Salahuddin; Quratulain Shaikh; Samreen Sarfaraz; Aneela Hussain; Aamir Sikander Kazi; Muhammad Hamid Hanif; Mujahid Hussain (PKLI Journal of Health Sciences, 2026)
Background: Antimicrobial resistance (AMR) is on the rise globally. One strategy proposed by WHO to curtail AMR includes establishing antimicrobial stewardship (AS) programs. The objective of this study was to describe the practices of antimicrobial use at the Indus Hospital and Health Network (IHHN) and share their experience of establishing an AS program. Methods: The Infectious Diseases (ID) department at IHHN, Korangi Campus, established an AS program in 2020. In the first phase (2020-2022), pharmacist-led reviews were performed on selected cases of injudicious antimicrobial use. In 2023, a prospective audit and feedback methodology was adopted. The data collected prospectively during these phases is analyzed in this paper. Frequencies and percentages were reported for categorical variables. SPSS 19 was used for data analysis. Results: A total of 789 cases were analyzed across both phases. Overall compliance with AS recommendations was approximately 80%. Seven out of nine departments showed improved adherence over time, with cardiology and nephrology achieving over 90% compliance. The majority of antimicrobials reviewed (79%) were categorized in the WHO Watch group. In 2023 alone, AS interventions led to a direct cost saving of PKR 2,441,682 (approximately USD 12,000) and prevented administration of at least 1,765 antimicrobial doses. De-escalation or discontinuation of empiric therapy after 72 hours was the most frequent recommendation. Notably, 40% of cases reviewed did not require any antibiotics. Conclusion: Implementing AS programs is crucial for monitoring and optimizing antimicrobial use. The IHHN model demonstrates the effectiveness of interdisciplinary collaboration, pharmacist-led reviews, and continuous education to promote rational antimicrobial use in a resource-limited setting.